Contesting institutional hegemony in today's business schools : doctoral students speak out - Prasad, Ajnesh (Emerald, 2016)
This book brings together a group of critically-orientated early career researchers from global business schools to investigate a series of timely questions pertaining to the impact that institutional pressures have on junior academics - particularly those who conduct 'critical' or non-mainstream research.
Keywords: Business education -- Research.; elektronické knihy; electronic books